The importance of post-analysis data processing in ICP-AES: calibration adjustment and multi-line approaches. Issue 11 (6th September 2018) - Baghdadi, S.; Crozet, M.; Gracia, S.; Dautheribes, J. L.; Rivier, C.; Picart, S.
Abstract : The effect of different post-analysis data processing approaches such as the "excess variance" approach was investigated for ICP-AES analyses. Abstract : This study presents post-analysis data processing that can be used in Inductively Coupled Plasma-Atomic Emission Spectrometry (ICP-AES). Two complementary methods were developed: the optimisation of the calibration curve and the use of the "Total Sum model". In order to work on a Certified Reference Material, the CETAMA "EQRAIN 22" solution was used. First, the effect of the computation model used was evaluated. The Total Sum model was developed using two approaches: a "classical" weighted mean and the "excess variance" weighted mean. The results show a decrease by a factor of about 4 for iron, and 2 for arsenic and palladium in uncertainties. Then, the effect of the calibration solution on both result uncertainties and method detection limits was studied. The study shows that using the appropriate calibration can reduce them by a factor of 10. Such results lead to a total gain in detection limits by a factor of about 30.